PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTIOXIDANT ACTIVITY OF DATURA STRAMONIUM L. COLLECTED FROM JIMMA, SOUTH WEST ETHIOPIA - KUMAR GANESAN; SURESH KUMAR P. NAIR; HENOK GULILAT AZALEWOR; NEETHU LETHA; SHARMILA BANU GANI (International Journal of Pharma and Bio Sciences, 2016)
The plant derived materials come into use in the contemporary medicine through aboriginal cure in traditional systems of medicine. Medicinal plants are chief antidote for numerous diseases and have been used since time immemorial. The present study was investigated to identify the preliminary phytochemical analysis of crude extracts of leaves, fruits and stem of Datura stramonium using aqueous, benzene & CCl4 as solvents and in vitro antioxidant activity of dry and fresh leaves of D. stramonium L. by using DPPH methods. The extracts were subjected to qualitative phytochemical screening using standard procedures. Three different extracts of leaves, stem and fruits of D. stramonium were found to contain various secondary metabolites like Triterpenoids, Steroids, Glycosides, Saponins, Alkaloids, Flavonoids and Tannins. The results of antioxidant properties of both fresh and dry extracts exemplified that aqueous has more potent free radical scavenging activity than the organic solvents; the absorbance of the prepared samples was measured using UV- visible spectroscopy at 520 nm wavelength. The phytochemicals generated data from the three crude extracts of D. stramonium may be used as tools for quality control of drugs in the future, for the healing of a diversity of disease conditions.